2016
DOI: 10.9790/2402-1008015356
|View full text |Cite
|
Sign up to set email alerts
|

Determinatıon Of The Level Of Knowledge Of Consumers About Food Additives

Abstract: Object: In this study, consumer awareness and safety perceptions of food additives have been identified through survey. Desing: To investigate the level of information to consumers about food additives conducted the survey with 300 people in the center of Tekirdag province between the months of June and July 2015. Before the start of the survey in addition to mutual, it has been tested for clarity and validity of the questions in the questionnaire to make corrections with 10 people. Research data were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
1
9
2
Order By: Relevance
“…Of the participants, 78.8% were female because the data collection area included many more females than males, in addition to females being more cooperative in filling out the surveys and their interest in the food additives subject. This is a similar result to Dr. Serap Kayışoğlu's study [8].…”
Section: Resultssupporting
confidence: 89%
“…Of the participants, 78.8% were female because the data collection area included many more females than males, in addition to females being more cooperative in filling out the surveys and their interest in the food additives subject. This is a similar result to Dr. Serap Kayışoğlu's study [8].…”
Section: Resultssupporting
confidence: 89%
“…Another study in Turkey found a link between having sufficient knowledge about food additives and the education level of respondents. Similarly, 26.3% of the respondents stated that they knew enough information about E numbers of food additives (Kayışoğlu and Coşkun, 2016). In the present study, we found that 46.4% of the respondents stated basic knowledge of food additives, although, only a quarter (25.6%) understood the E numbers.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Do you know what food additives are?This was to determine how consumers assessed their own level of understanding of food additives. Because knowledge of food additives is important to enable consumers' worries to understand risk-benefit-appraisals, and to focus on the consumer and food production(Bearth et al, 2014;Bearth and Siegrist, 2016;Kayıs o glu and Cos kun, 2016;Ismail et al, 2017). (…”
mentioning
confidence: 99%
“…A questionnaire was developed to inquire about consumers’ knowledge and safety perceptions regarding FAs. The questions/scales were adopted from previously validated surveys in published literature [ 8 , 9 , 13 , 16 , 17 ]. It consisted of 37 questions, categorized into 6 sub-sections.…”
Section: Methodsmentioning
confidence: 99%
“…Their usage has been plagued with several health concerns ranging from allergy to cancer [ 6 , 7 ]. Few studies which assess consumers’ knowledge and safety perceptions regarding FAs have been conducted previously [ 8 , 9 ]. Inadequate knowledge could be associated with negative attitude concerning FAs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%